Wiedza w organizacjach sieciowych - opis formalny - Maj, Ireneusz (Knowledge in Network Organizations - a Formal Discretion, 2005)
A future-oriented network organization cancels traditional hierarchical structures, thus invalidating knowledge as a source of power, and removing barriers to its distribution. Linkages between network organization's elements make it possible to directly communicate, in a manner oriented towards tasks, not power. We describe knowledge in a network organization using general systemic approach pointing out the process of organization's dynamic adaptation to changing background conditions as one expressed by categories of knowledge which is the main determinant of organization's competition advantage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 99-107